2022
DOI: 10.1016/j.neuropsychologia.2022.108166
|View full text |Cite
|
Sign up to set email alerts
|

Iconicity in sign language production: Task matters

Abstract: The present study explored the influence of iconicity on sign lexical retrieval and whether it is modulated by the task at hand. Lexical frequency was also manipulated to have an index of lexical processing during sign production. Behavioural and electrophysiological measures (ERPs) were collected from 22 Deaf bimodal bilinguals while performing a picture naming task in Catalan Sign Language (Llengua de Signes Catalana, LSC) and a word-to-sign translation task (Spanish written-words to LSC). Iconicity effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 52 publications
4
13
3
Order By: Relevance
“…The results, however, stand in contrast to previous sign recognition studies reporting a lack of iconicity effects on ERPs [11,15]. Iconicity effects may be modulated by task requirements, in a way that they would arise when the task emphasizes or taps into semantic activation [16]. The semantic decision task here focused specifically on meaning properties and might thus lead to greater semantic activation than the translation task used in [15], prompting the use of iconicity even during the early stages of sign recognition.…”
Section: Iconicitycontrasting
confidence: 99%
See 2 more Smart Citations
“…The results, however, stand in contrast to previous sign recognition studies reporting a lack of iconicity effects on ERPs [11,15]. Iconicity effects may be modulated by task requirements, in a way that they would arise when the task emphasizes or taps into semantic activation [16]. The semantic decision task here focused specifically on meaning properties and might thus lead to greater semantic activation than the translation task used in [15], prompting the use of iconicity even during the early stages of sign recognition.…”
Section: Iconicitycontrasting
confidence: 99%
“…The iconicity effects originated early in time, in line with prior reports in sign production [16] (though with different polarity), suggesting that iconicity may confer an advantage during the early stages of lexical processing. The results, however, stand in contrast to previous sign recognition studies reporting a lack of iconicity effects on ERPs [11,15].…”
Section: Iconicitysupporting
confidence: 87%
See 1 more Smart Citation
“…Recent studies also indicate that iconicity can impact both sign recognition (Vinson et al, 2015) and production (Sehyr & Emmorey, 2022). However, iconicity effects are not always observed, and some effects of iconicity may be task specific (Gimeno-Martínez & Baus, 2022). Further, many variables have yet to be fully investigated, such as the type of iconicity, the role of language proficiency, and how iconic mappings are construed.…”
Section: Iconicity Is Pervasive In Sign Language Lexicons and Can Pla...mentioning
confidence: 99%
“… Vinson et al (2015) found that pictures that elicited iconic British Sign Language (BSL) signs were named more quickly than those that elicited non-iconic BSL signs. Faster picture-naming for iconic signs has now been replicated across other signed languages, including Italian Sign Language (LIS; Navarrete et al, 2017 ; Pretato et al, 2018 ), ASL ( McGarry et al, 2020 ; Sehyr and Emmorey, 2022 ), and Catalan Sign Language (LSC; Baus and Costa, 2015 ; Gimeno-Martínez and Baus, 2022 ).…”
mentioning
confidence: 98%